High Prevalence of Hypovitaminosis D in Cutaneous and Systemic Lupus Erythematosus Patients and Its Associated Factors: A Cross-Sectional Study in Thailand - Kanokrungsee S; Patcharapojanart C; Suchonwanit P; Chanprapaph K (Dove Medical Press, 2022)
Silada Kanokrungsee, Chanikarn Patcharapojanart, Poonkiat Suchonwanit, Kumutnart Chanprapaph Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Kumutnart Chanprapaph, Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama IV Road, Bangkok, 10400, Thailand, Tel +66 626393659, Email kumutnartp@hotmail.comObjective: To investigate the prevalence of low vitamin D levels in patients with cutaneous lupus erythematosus (CLE) and systemic lupus erythematosus (SLE) in Thailand and determine the influential factors associated with inadequate levels.Methods: The medical records of patients diagnosed with SLE and/or CLE and evaluated for serum 25-OH vitamin D were retrospectively reviewed from January 2014 to January 2021. Vitamin D deficiency (< 20 ng/mL) and insufficiency (21- 29 ng/mL) were indicated, and predictors of hypovitaminosis D were identified by multiple linear regression analysis.Results: In total, 414 patients with SLE and/or CLE were included in the study. Vitamin D deficiency was predominant in the CLE-only group (33.3%), followed by SLE without CLE (15.6%) and SLE with CLE (8%), p < 0.001. Likewise, vitamin D insufficiency was more prevalent in the CLE-only group (44.4%) compared to SLE with (35.8%) and without CLE (40%). Multivariate analysis showed that a higher SLEDAI-2K score and female sex had a negative association with vitamin D levels, while an intake of every 10,000 IU of vitamin D2 per week increased serum vitamin D levels by up to 2.37 ng/mL. Furthermore, forty-five percent of patients continued to have vitamin D depletion despite commencing the recommended doses of vitamin D replacement.Conclusion: Approximately half of Thai patients with SLE and 80% of CLE had vitamin D inadequacy. Vitamin D replacement is a good predictor of high serum vitamin D levels, while lower serum levels were associated with higher disease severity. Therefore, serum vitamin D monitoring and supplementation are suggested for all lupus erythematosus cases, especially those with CLE.Keywords: 25(OH) vitamin D, cutaneous lupus erythematosus, lupus, systemic lupus erythematosus, vitamin D status